Theories of pain: from specificity to gate control - Moayedi, Massieh; Davis, Karen D. (Journal of neurophysiology, 2013)
Several theoretical frameworks have been proposed to explain the physiological basis of pain, although none yet completely accounts for all aspects of pain perception. Here, we provide a historical overview of the major contributions, ideas, and competing theories of pain from ancient civilizations to Melzack and Wall's Gate Control Theory of Pain.